KEPEMIMPINAN RELIGIUS DALAM IMPLEMENTASI KEBIJAKAN PENUTUPAN TEMPAT HIBURAN (KARAOKE) (STUDI KASUS KEBIJAKAN WALIKOTA MENUTUP TEMPAT HIBURAN (KARAOKE) DI KOTA PROBOLINGGO) - Marwiyah, Siti; Puspitarini, Renny Candradewi; Solihin, Muhammad Hindun (Universitas Jabal Ghafur, 2023)
Leaders have a mandate to carry out their obligations in accordance with their position and position, and follow applicable regulations. Leadership is also related to the background of understanding of religion, so that in making policies accompanied by religious values. Thus, religious leadership is realized. A phenomenon related to the religious leadership model and policy is the phenomenon related to the license of entertainment venues. As in the city of Probolinggo, which also issued a policy on entertainment place licenses. issued Perda Number 9 of 2015 concerning the Arrangement, Supervision and Control of Entertainment Place Businesses. This is interesting to study, especially with the five-dimensional theory, including ideology; intellectual; public practice; private practice; religious experience. The results showed that the leadership of the Mayor of Probolinggo for the 2019-2024 period implemented a policy of closing karaoke places in Probolinggo City. The policy illustrates a religious leadership model. The point is that the mechanism for closing karaoke places applies the principles of democracy and is related to the understanding of religion by the Mayor of Probolinggo. And there is a violation of Regional Regulation Number 9 of 2015 concerning Arrangement, Supervision, and Control of Entertainment Places. This policy does not only benefit one religion, but for religious harmony. It is not only the Muslim community that thinks badly of karoke places, but other religions as well. There are even karoke venues located in public places that are still close to schools and places of worship. In addition, it was found that there is the provision of song accompaniment when karaoke, the dress of guests and employees is not polite, and there is the sale and purchase of alcoholic beverages.Keywords : religious leadership, policies, entertainment permits